Análise morfológica e filogeográfica em jabutis brasileiros (Testudines) - Silva, Tiago Lucena da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study evaluated associated data on biogeography, vocalization, morphology, cytogenetics, hemoglobin and molecular profile using cytochrome b, from Brazilian tortoises in order to explore the discriminative potential of the evaluated taxonomic techniques. In Brazil, two species of tortoises are described, C. carbonarius and C. denticulatus, however, some animals initially recognized based on morphological characters and coloring did not correspond to the typical pattern of C. carbonarius, being classified as morphotypes 1 and 2. The proposed hypothesis in this study is that the morphotypes are already differentiated species and should not be considered as a single taxonomic unit with C. carbonarius. Tortoises from the National Institute for Amazonian Research (INPA), Emilio Goeldi Museum - PA, municipal zoos of São José do Rio Preto - SP and Araçatuba - SP and Reginaldo Uvo Leone breeding farm for Wild and Exotic Animals in Tabapuã - SP, were analyzed. Based on the data obtained by biogeographic evaluation of specimens in the literature, it was found that the distribution of C. carbonarius is associated with the Northeast region, with no animals deposited in the visited collections. In Brazil, C. denticulatus occurs in all states of the Amazonia Legal besides presenting isolated individual records for the domain of the Atlantic Forest in the states of Espirito Santo and Rio de Janeiro, and in the Midwest region in the states of Goias, Mato Grosso and Mato Grosso do Sul. In the Northeast region, it occurrs in the state of Bahia. The morphotype 1 has a wider geographical distribution than C. carbonarius, and it is possibly attributed to several reports distribution associated with C. carbonarius, indicating erroneous association of morphotype 1 as a single taxonomic unit with C. carbonarius. The morphotype 2 was observed only in the states of Pará, Maranhão and Piauí. These data indicate that part of the allocated distribution..

Esse estudo avaliou dados sobre: biogeografia, vocalização, morfologia, citogenética, perfil de hemoglobinas e do marcador molecular citocromo b em jabutis brasileiros, no intuito de explorar o potencial taxonômico discriminativo das metodologias avaliadas. Duas espécies de jabutis são descritas para o Brasil, sendo elas, C. denticulatus e C. carbonarius, entretanto, observou-se, inicialmente com base em caracteres morfológicos e de coloração, a existência de populações que não correspondiam ao padrão típico da espécie C. carbonarius, sendo classificados neste estudo como morfotipos 1 e 2. A hipótese proposta é que os morfotipos correspondam a espécies já diferenciadas, e que não devem ser consideradas como uma mesma unidade taxonômica que C. carbonarius. Foram avaliados jabutis depositados no Instituto Nacional de Pesquisas da Amazônia (INPA) e no Museu Paraense Emílio Goeldi, nos bosques municipais de São José do Rio Preto - SP e Araçatuba - SP e no Criatório de Animais Silvestres e Exóticos Reginaldo Uvo Leone em Tabapuã - SP. Com base nos dados obtidos pela avaliação biogeográfica dos espécimes na literatura, observou-se que, a distribuição da espécie C. carbonarius está associado à região Nordeste do país, não havendo no entanto, espécimes depositados nas coleções visitadas. No Brasil, C. denticulatus ocorre em todos os estados da Amazônia Legal, além de apresentar registros isolados para o domínio da Floresta Atlântica, nos estados do Espírito Santo e do Rio de Janeiro, e para a região Centro-Oeste, nos estados de Goiás, Mato Grosso e Mato Grosso do Sul. Na região Nordeste, apresenta ocorrência no estado da Bahia. O morfotipo 1, apresenta distribuição geográfica mais abrangente que C. carbonarius e possivelmente é atribuído a ele, os relatos de distribuição associados a C. carbonarius, indicando associação equivocada do morfotipo 1 como uma mesma unidade taxonômica...
Keywords: Biologia; Biologia - Classificação; Tartaruga - Biogeografia - Brasil; Animais - Comportamento; Hemoglobina; Citogenética animal